Histamine and its “allergic” receptors - Fernandes, João Paulo S. (Henry Stewart Talks, 2023)
Histamine receptors, Allergic reactions, 2nd generation antihistamines, Histamine storage and release, Histamine and the immune system, Asthma, Inflammatory bowel disease, H1 and H4 antihistamines, Clinical trials